Tau Protein and Adult Hippocampal Neurogenesis - Fuster-Matanzo, Almudena; Llorens-Martín, María; Jurado-Arjona, Jerónimo; Avila, Jesus; Hernández, Félix (Frontiers in Neuroscience, 2012)
Tau protein is a microtubule associated protein found in the axonal compartment that stabilizes neuronal microtubules under normal physiological conditions. Tau metabolism has attracted much attention because of its role in neurodegenerative disorders called tauopathies, mainly Alzheimer disease. Here, we review recent findings suggesting that axonal outgrowth in subgranular zone during adult hippocampal neurogenesis requires a dynamic microtubule network and tau protein facilitates to maintain that dynamic cytoskeleton. Those functions are carried out in part by tau isoform with only three microtubule-binding domains (without exon 10) and by presence of hypherphosphorylated tau forms. Thus, tau is a good marker and a valuable tool to study new axons in adult neurogenesis.